Phytochemical study of shells schinus Terebinthifolius raddi (anacardiaceae) - Lima, Renato Abreu; Silva, Livia Rosiane; Andrade, Alice Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The objective of this study was to conduct a phytochemical study and analyzes the secondary metabolites of plant extract of the shell of S. terebinthifolius. The methodology used to obtain the extract was made from the appropriately dried and crushed shells which were placed in conical flask containing one liter of ethanol for seven days. Then, the material was filtered and subjected to simple distillation process to obtain the syrup and after conducted the tests for identification of secondary metabolites. It was found that the ethanolic extract of the shell of secondary metabolites have great interest in the pharmaceutical industry.